Surfactant protein D regulates caspase-8-mediated cascade of the intrinsic pathway of apoptosis while promoting bleb formation. (December 2017) - Djiadeu, Pascal; Farmakovski, Nicole; Azzouz, Dhia; Kotra, Lakshmi P.; Sweezey, Neil; Palaniyar, Nades
Highlights: An innate immune collectin differentially regulates specific steps of apoptosis. SP-D suppresses the caspase-8, but not caspase-9 branch of the UV-induced apoptosis. However, SP-D promotes effective blebbing and breakdown of dying cells. Abstract: Surfactant-associated protein D (SP-D) is a soluble innate immune collectin present on many mucosal surfaces. We recently showed that SP-D suppresses the extrinsic pathway of apoptosis by downregulating caspase-8 activation. However, the effects of SP-D on the intrinsic pathway of apoptosis are not clearly understood. In the intrinsic pathway, cytochrome c is released by mitochondria into the cytoplasm. Oxidation of cytochrome c by cytochrome c oxidase activates the apoptosome and caspase-9 cascade. Both caspase-8- and caspase-9-mediated branches are activated in the intrinsic pathway of apoptosis; however, little is known about the relevance of the caspase-8 pathway in this context. Here we studied the effects of SP-D on different branches of the intrinsic pathway of apoptosis using UV-irradiated Jurkat T-cells. We found that SP-D does not inhibit the caspase-9 branch of apoptosis and the relevance of the caspase-8-related branch became apparent when the caspase-9 pathway was inhibited by blocking cytochrome c oxidase. Under these conditions, SP-D reduces the activation of caspase-8, executioner caspase-3 and exposure of phosphatidylserine (PS) on the membranes of dying cells. By contrast, SP-D increases the formation of nuclear and membrane blebs. Inhibition of caspase-8 confirms the effect of SP-D is unique to the caspase-8 pathway. Overall, SP-D suppresses certain aspects of the intrinsic pathway of apoptosis via reduction of caspase-8 activation and PS flipping while at the same time increasing membrane and nuclear bleb formation. This novel regulatory aspect of SP-D could help to regulate intrinsic pathway of apoptosis to promote effective blebbing and breakdown of dying cells.